Hypericum perryongii (Hypericaceae), a new species from Philippines - Galindon, John Michael M.; Penneys, Darin S.; Lagunday, Noel E.; Tandang, Danilo N.; Coritico, Fulgent P.; Amoroso, Victor B.; Fritsch, Peter W. (Phytotaxa, 2021)
Hypericum perryongii, from Mindanao Island, Philippines, is herein described and illustrated. This new taxon closely resembles both H. geminiflorum and H. formosanum but can be easily distinguished from the former by its larger corolla and calyx lobes and higher number of stamens per fascicle, and from the latter by its terminally 1-flowered inflorescences and the subsessile and abaxially glaucous leaves.